Penyuluhan motivasi belajar dan pembagian alat tulis kepada siswa sekolah dasar di Kampung Sairo, Distrik Manokwari Utara: Counseling on learning motivation and distribution of stationary to primary school students in Sairo Vilage, North Manokwari District - Santoso, Budi; Nunaki, Jan H.; Rumatumia, Zainudin; Ick, Loisa A.; Inggesi, Barsalina J. (IGKOJEI: Jurnal Pengabdian Masyarakat, 2024)
ABSTRACT  The success of the educational process is largely determined by teachers, students and the school environment. In the learning process, learning motivation is a very important dynamic aspect. The aim of this counseling was to provide motivation/encouragement for learning and at the same time provide stationery assistance which aims to support the learning process for students at SD Inpres 61 Mandopi, Sairo Village. This counseling was carried out at the Inpres 61 Mandopi Elementary School, Sairo Village, North Manokwari District. This activity was attended by 29 people consisting of 27 students and 2 teachers. This activity was carried out in 2 stages, namely the preparation stage and the counseling stage. Counseling was carried out using lecture and discussion methods using visual media tools, point slides and videos. The results of the activity showed that the counseling participants were very enthusiastic about participating in this activity, which was indicated by the activeness of the students when answering several questions from the Service Team. To obtain optimal learning results, teachers are required to be creative in generating student learning motivation. At the end of the activity, stationery assistance was handed over to the head of school and distribution of stationery to students. It was concluded that the counseling activities carried out at the Inpres 61 Mandopi Primary School, Sairo Village had run smoothly and received a positive and enthusiastic response from teachers and students participating in the counseling. Motivation is one of the factors that influences student success in the learning process.  Keywords: Counseling; Motivation; Sairo; Study; Student   ABSTRAK Keberhasilan proses pendidikan sangat ditentukan oleh guru, siswa dan lingkungan sekolah. Pada proses pembelajaran motivasi belajar merupakan salah satu aspek dinamis yang sangat penting.  Tujuan penyuluhan ini adalah memberikan motivasi/dorongan belajar dan sekaligus memberikan bantuan alat tulis yang bertujuan untuk mendukung proses pembelajaran bagi siswa/siswi di SD Inpres 61 Mandopi, Kampung Sairo.  Penyuluhan ini dilaksanakan di Sekolah Dasar Inpres 61 Mandopi Kampung Sairo, Distrik Manokwari Utara.  Kegiatan ini diikuti 29 orang terdiri atas 27 orang siswa dan 2 orang guru.  Kegiatan ini dilaksanakan melalui 2 tahap yaitu tahap persiapan dan tahap penyuluhan.  Penyuluhan dilakukan menggunakan metode ceramah dan diskusi dengan menggunakan alat bantu media visual berupa slide power point dan video.  Hasil kegiatan menunjukkan peserta penyuluhan sangat antusias mengikuti kegiatan ini yang diindikasikan dengan keaktifan siswa/siswi ketika menjawab beberapa pertanyaan dari Tim Pengabdi.  Untuk memperoleh hasil belajar yang optimal, guru dituntut kreatif membangkitkan motivasi belajar siswa.  Pada akhir kegiatan dilakukan penyerahan bantuan alat tulis kepada kepala sekolah dan pembagian alat tulis kepada siswa.  Disimpulkan bahwa kegiatan penyuluhan yang dilaksanakan di Sekolah Dasar Inpres 61 Mandopi, Kampung Sairo telah berjalan dengan lancar dan mendapat sambutan positif dan antusias dari guru dan siswa/siswi peserta penyuluhan. Motivasi merupakan salah satu faktor yang mempengaruhi keberhasilan siswa dalam proses pembelajaran. Kata kunci: Belajar; Motivasi; Penyuluhan; Sairo; Siswa